2020
DOI: 10.1371/journal.pone.0233188
|View full text |Cite
|
Sign up to set email alerts
|

Survival of glioblastoma treated with a moderately escalated radiation dose—Results of a retrospective analysis

Abstract: Glioblastoma (GBM) has the highest fatality rate among primary malignant brain tumors and typically tends to recur locally just adjacent to the original tumor site following surgical resection and adjuvant radiotherapy. We conducted a study to evaluate the survival outcomes between a standard dose (� 60 Gy) and moderate radiation dose escalation (>60 Gy), and to identify prognostic factors for GBM. We retrospectively reviewed the medical records of primary GBM patients diagnosed between 2005 and 2016 in two re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…Further, the more recently defined subtype of epithelioid GBM, there were no registered case data in the study. It is well-known a younger age is significantly associated with good survival in conventional GBM patients in the literature (6,20,(26)(27)(28). A younger age experienced favorable survival in our GBM cohort.…”
Section: Discussionmentioning
confidence: 54%
“…Further, the more recently defined subtype of epithelioid GBM, there were no registered case data in the study. It is well-known a younger age is significantly associated with good survival in conventional GBM patients in the literature (6,20,(26)(27)(28). A younger age experienced favorable survival in our GBM cohort.…”
Section: Discussionmentioning
confidence: 54%
“…Currently, for the treatment on GBM patients, surgery and chemo- or radiotherapy were the main available methods [ 2 4 ]. But the resistance to chemo- or radiotherapy was the trouble of the clinical treatment on these patients, which may reduce therapeutic efficacy or enhance the toxicity to normal organs by increasing the therapeutic dosage with poor long-term survival for patients [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma is an aggressive brain tumor with shorter median overall survival time in adults [ 1 ], although multiple therapeutic methods have been used including surgical resection and chemo- or radiotherapy [ 2 , 3 ]. It has been reported that only a median survival of 15 months was obtained after radiotherapy combined with temozolomide (TMZ) [ 4 , 5 ], which was the major chemotherapy drug for GBM but with resistance effects for most patients yet [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is the preferred treatment for patients with glioma. Postoperative radiotherapy has been shown to improve intracranial local control and overall survival (OS) time of patients with glioma [8,9]. Although timely surgery and radiotherapy have improved the survival and protected the nervous system of patients with glioma, their prognosis remains poor.…”
Section: Introductionmentioning
confidence: 99%